Muhammadiyah Non-Formal Education During the Covid 19 Pandemic - Nur Fazriya Masfufa; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
Non-formal education is practical education or training for the community that is still carried out by the community to increase knowledge and increase interest in talent in themselves. The purpose of this study is to find out about Muhammadiyah non-formal education, the goals and benefits of non-formal education, the characteristics of Muhammadiyah non-formal education and forms of non-formal education of Muhammadiyah. The data collection techniques were interviews and observations, interviews with resource persons Mrs. Sumjiana (managers) and observations and research at the Muhammadiyah branch of the Muhammadiyah College in Gedangan District. This study uses descriptive qualitative research methods. A qualitative approach is a research process to understand social or human problems by analyzing words to create a complex and comprehensive picture, as well as reporting detailed information views obtained from information sources in the natural environment. Muhammadiyah non-formal education during the COVID-19 pandemic took various forms. Muhammadiyah non-formal education such as TK Aisyah 1 Gedangan and TPQ Tunas Jasmine in Gedangan District.